HDL-associated enzymes and proteins in hemodialysis patients - Cacciagiú, Leonardo D. (2012)
OBJECTIVES: To evaluate HDL-associated proteins and enzymes and their relation with lipoprotein profile and inflammatory markers in chronic renal patients on hemodialysis. DESIGN AND METHODS: We studied 53 patients under hemodialysis and 32 healthy subjects as controls. We compared plasma lipids, Apoprotein-AI and hs-CRP, as a marker of chronic inflammation. We evaluated proteins and enzymes associated to HDL, involved in several points of lipoprotein metabolism: CETP, paraoxonase and LpPLA2 activities. Hepatic lipase was measured in postheparin plasma. RESULTS: Patients showed higher triglycerides and lower LDL-, HDL- and total-cholesterol than controls (p<0.05). Also, in comparison with controls, Apoprotein-AI, paraoxonase and hepatic lipase were lower, while CETP was higher (p<0.03). LpPLA2 did not show changes between groups. CONCLUSION: Beyond plasma lipid-lipoprotein profile, other factors could contribute to induce a pro-oxidative and pro-inflammatory status. The protective role of HDL does not only depend on its concentration, but also on its functionality.